Perspectivas decoloniales/metodologías horizontales. Construyendo espacios de discusión-acción alternativos en la escuela (Experiencias) - Santos Gutiérrez, Cristhian Ricardo (2022)
The article presents the results of the research project entitled De las aulas pal barrio: critical readings and alternative social practices. The project proposed to respond to the pressing need to articulate critically the teaching-learning processes prevailing today in the school —limited by an institutionalized logic of educational practices— and the contextual needs of the subjects in training who are immersed in these processes. The elements of the research project exposed here are framed within the limits of a ‘decolonial epistemological approach’ and ‘horizontal methodologies’ as a guiding element for its development. Furthermore, as a result of the project, the inter/transdisciplinary exercises that were carried out as a practical proposal are presented within the academic spaces built for ‘alternative discussion-action’ and how these are articulated with the institutional demands, but at the same time, how they transcend them, enabling thus a greater approach to the contextual needs of the subjects in training. Finally, some conclusions are proposed that highlight the importance of the ‘decolonial epistemological approach’, ‘horizontal methodologies’, the need for inter/transdisciplinary educational practices, and ‘alternative discussion-action’ spaces as an articulation mechanism between school and society.